(untitled) (BIRDEM Medical Journal, 2025)
Clozapine is a second-generation antipsychotic with proven efficacy in treatment-resistant schizophrenia, but its use is constrained by serious hematologic side effects, notably agranulocytosis. While bicytopenia denotes simultaneous reduction in two blood cell lines which is an uncommon and potentially underrecognized adverse event during clozapine therapy. We report a case of a 17-year-old male diagnosed with schizophreniform disorder who developed clozapine[1] induced bicytopenia. After inadequate response to paliperidone 6 mg/day, quetiapine 300mg/day, clozapine was initiated and titrated up to 200 mg/day over 14 days. The patient showed symptomatic clinical improvement; however, two weeks after initiation, he developed fever and laboratory evaluation revealed leukopenia (White blood cell 3500/mm³, Absolute neutrophil count 1435/mm³), while red blood cell count and platelet count remained within normal limits initially. Clozapine was promptly discontinued. Despite partial recovery in WBC and ANC, RBC and Hb levels continued to decline with values reaching 9.9 g/dL and 3.54 million/ìL, respectively. Hematologic workup including lactate dehydrogenase (LDH), direct and indirect Coombs tests, and absolute reticulocyte count excluded hemolysis or autoimmune etiology. The patient was subsequently started on roxadustat 70 mg, an erythropoiesis-stimulating agent. Hematologic parameters normalized within four weeks. At the same time patient was suffering from inflammatory skin condition and was being treated with triazole antifungal. In this case, systemic inflammation and a potential drug interaction with itraconazole at a dosage of 65 mg, two tablets daily (total daily dose: 130 mg); may have been contributing factors to clozapine-induced bicytopenia. This case underscores the importance of extending routine hematologic monitoring in patients receiving clozapine beyond white blood cell (WBC) and absolute neutrophil count (ANC) to include comprehensive blood count parameters, enabling early detection of rare hematologic abnormalities and prevention of serious complications. BIRDEM Med J 2025; 15(3): 150-154